The Culture of Business Education and its Place in the Modern University - Evans, Russell Alex (Canadian Journal of Higher Education, 2015)
Many researchers believe that the modern university is in a state of crisis like never before. One of the main reasons cited for this decline is that the modern university has a closer resemblance to a transnational corporation than to a traditional scholarly institution (Lewis, 2005). This paper attempts to define the term “university” from a classical perspective and to describe the gradual incorporation of vocational pursuits into its scope. Focusing on modern North American university models, it asks whether business schools, in particular, should be operating within academia. An alternative is discussed, which focuses on the vocational attributes of business rather than theoretical knowledge. I draw on secondary sources as well as my own personal experience as a student and researcher to make suggestions on how interdepartmental tension developed and how it can be reduced. The paper finds that the business school does have a place in the modern university; however, the classical representation of the university must be abandoned for it to be fully embraced.